Barefoot : a story of surrendering to God - Brown, Sharon Garlough (Brown, Sharon Garlough. Sensible shoes, 2016)
The spiritual journey takes unexpected turns for the women of Sensible Shoes in this third book of the series. Having been challenged to persevere in hope, can they now embrace the joy of complete surrender? Join these four women in a poignant story that reveals the joy that comes from laying our lives at the feet of God and standing barefoot on holy ground.